Type sequences of one-dimensional local analytically irreducible rings - Barucci, Valentina; Serban, Ioana Cristina (MATHEMATICA SCANDINAVICA, 2012)
We extend the notion of type sequence to rings that are not necessarily residually rational. Using this invariant we characterize different types of rings as almost Gorenstein rings and rings of maximal length.